Unraveling the venom components of an encyrtid endoparasitoid wasp Diversinervus elegans. (15th September 2017) - Liu, Nai-Yong; Wang, Jin-Qiang; Zhang, Zu-Bing; Huang, Jing-Mei; Zhu, Jia-Ying
Abstract: The encyrtid parasitoid, Diversinervus elegans (Hymenoptera: Encyrtidae), is a natural enemy of the notorious scale pests belonging to the family of Coccidae. Venom containing a rich source of bioactive molecules is a key virulent factor used to regulate host physiology by parasitoids. Although knowledge regarding venom constituents accumulated from limited parasitoids has provided insights into their roles in host-parasitoid interaction, toxins involving in manipulating scale physiology remain sparsely documented. Here, a total number of 48 putative venom proteins were identified from D. elegans using an integrative transcriptomic and proteomic approach. The majority of them such as serine protease, esterase, and major royal jelly protein have been found in venom of other several parasitoid species. Several venom proteins including three novel proteins having unknown function were firstly revealed. Quantitative real time PCR analysis demonstrated that 16 venom genes displayed female-biased expression, which might be important for parasitism success. These data enrich our understanding of parasitoid venom evolution and diversity, and will undoubtedly help deciphering functional venom proteins as potential candidates for pest control. Graphical abstract: Highlights: Integrative transcriptome and proteome approach was used to reveal venom composition of D. elegans . Putative 48 venom proteins were identified. Sex biased expression of identified venom genes were analyzed. Venomics information of D. elegans will facilitate to discover functional toxins.